2003
DOI: 10.1046/j.1365-2222.2003.01712.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CS‐1 fibronectin precedes monocyte chemoattractant protein‐1 production during elicitation of allergic contact dermatitis

Abstract: We showed evidence of the fact that CS-1 fibronectin expression precedes the production of MCP-1/CCL2 and TARC/CCL17 in the skin of patients with ACD, suggesting that these molecules participate in the early complex process of migrating mononuclear cells during elicitation of ACD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Of note, this synergism occurs also in the opposite direction: CCL7 synergizes with CCL19 and CCL21 on CCR7-transfected cells as well as on mature dendritic cells, as we previously described [9]. A meeting place of both homeostatic and inflammatory chemokines is HEV where CCL19 and CCL21 are both expressed [26], and CCL2 and CCL7 [20,42] are transported from inflamed tissue to trigger arrest of rolling monocytes [32]. Therefore, the CCR7 and the CCR2 agonists meet the criteria to be at the same place and at the same time to enhance the migration of CCR2 1 cells in vivo.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Of note, this synergism occurs also in the opposite direction: CCL7 synergizes with CCL19 and CCL21 on CCR7-transfected cells as well as on mature dendritic cells, as we previously described [9]. A meeting place of both homeostatic and inflammatory chemokines is HEV where CCL19 and CCL21 are both expressed [26], and CCL2 and CCL7 [20,42] are transported from inflamed tissue to trigger arrest of rolling monocytes [32]. Therefore, the CCR7 and the CCR2 agonists meet the criteria to be at the same place and at the same time to enhance the migration of CCR2 1 cells in vivo.…”
Section: Discussionsupporting
confidence: 51%
“…Most leukocytes express more than one chemokine receptor and, hence, can respond to more than one chemokine. Additionally, a great variety of in situ experiments demonstrated the concomitant expression of chemokines at target sites of leukocyte trafficking and homing [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contact allergens and irritants can directly induce the expression of both TNF-α and MCP-1 [23] that may explain increased serum levels of these cytokines in patients with ACD. For example, Martin et al [24] have demonstrated the expression of MCP-1 by basal keratinocytes and isolated dermal cells at 10 h after antigen challenge, paralleled by dermal accumulation of mononuclear cells. TNF-α may contribute to the rise in MCP-1 by stimulating fibroblasts, endothelial cells, macrophages and dendritic cells to produce MCP-1 alongside with several other cytokines [24], which might explain remarkably high serum MCP-1 levels in patients with ACD.…”
Section: Discussionmentioning
confidence: 99%